Perancangan Mesin Pengaduk Media Tanam Jamur Tiram Dengan Pendekatan Metode NIDA - Falah, Muhamad Miftakhul; Izzhati, Dwi Nurul (Universitas Kadiri, 2026)
Indonesia has significant agrarian potential, with oyster mushrooms as a high-value economic and nutritious commodity. Production is supported by 25.1 million farming households and 17.2 million smallholder farmers, yielding 43.36 million kg annually. This study aims to design a log bag production machine capable of producing >38 kg per batch, equipped with a 6.5 HP motor and a 200 L drum, with a total manufacturing cost of <IDR 3,800,000 and a potential profit margin >18%. A quantitative case study methodology was applied to the